Behavioral ethics: a story of increased breadth and depth. (December 2015) - Tenbrunsel, Ann E; Chugh, Dolly
Highlights: We review recent articles in behavioral ethics, noting increased breadth and depth. Increased depth is seen in research on the self and the intentionality of behavior. Increased breadth includes integration of non-self actors, justice and personality. Abstract : As the narrative of the behavioral ethics field continues to unfold, we take pause to note the recent research in this domain, highlighting areas of increased depth and increased breadth. Depth is revealed in the growing literatures focused on the role of the self in ethical decision-making and the distinction between intentional and unintentional unethical behavior. Breadth is revealed in work that considers the role others play in our ethical judgments, perceptions and attributions, an emerging bridge between fairness and ethics literatures, and a return to personality-based theories of ethics. We conclude with a call for more macro and interdisciplinary perspectives, as well as greater attention to theory building and ethics education.